Identity based and key insulated cryptosystem - ZHOU Yuan1; QIN Bao-shan 2; CAO Zhen-fu 3 (Tongxin xuebao)
The method of key insulation to identity-cryptosystems was applied,for solving the key exposure problem ex-isting in the identity-based schemes were applied.After developing the formal secure model for identity-based and key insulated cryptosystems,a concrete scheme proved secure under this model was constructed.